Bilateral red ears: Milian ear sign - Sayantani Chakraborty; Dibyendu Bikash Bhanja; Abheek Sil (Wolters Kluwer Medknow Publications, 2021)
Milian ear sign is a specific clinical finding that aides in differentiating erysipelas from facial cellulitis. The anatomical absence of subcutaneous tissue in pinna brings about this clinical distinction. Although bilateral Milian ear sign is rare, erysipelas should be considered when encountering patients presenting with red ears, among other differentials such as Ramsay-Hunt syndrome, relapsing polychondritis, auricular perichondritis, and red ear syndrome.